MR – eyes for cancer: looking within an impenetrable disease. (20th June 2013) - Penet, Marie‐France; Artemov, Dmitri; Farahani, Keyvan; Bhujwalla, Zaver M.; Mulder, Willem J. M.; McMahon, Michael T.; Nicolay, Klaas
Abstract : Probe development is a critical component in cancer imaging, and novel probes are making major inroads in several aspects of cancer detection and image‐guided treatments. Intrinsic MR probes such as signals from metabolites and their chemical shifts have been used for more than a decade to understand cancer physiology and metabolism. Through the integration of technology, molecular biology, and chemistry, the last few years have witnessed an explosion of extrinsic probes for molecular and functional imaging of cancer that, together with techniques such as CEST and hyperpolarization, have significantly expanded the repertoire of MR techniques in basic and translational investigations of many different aspects of cancer. Furthermore, incorporation of MR probes into multifunctional nanoparticles and multimodality imaging platforms have opened new opportunities for MR in image‐guided diagnosis and therapy of cancer. Here we have provided an overview of recent innovations that have occurred in the development of MRI probes for molecular and functional imaging of cancer. Although most of these novel probes are not clinically available, they offer significant promise for future translational applications. In this review, we have highlighted the areas of future development that are likely to have a profound impact on cancer detection and treatment. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Probe development is a critical component in cancer imaging, and novel probes are making major inroads in several aspects of cancer detection and image‐guided treatments. In this review, we have provided an overview of recent innovations that have occurred in the development of MRI probes for molecular and functional imaging of cancer. Although most of these novel probes are not clinically available, they offer significant promise for future translational applications.